Review of general psychiatry - Goldman, Howard H. (Lange Medical Publications, 1984)
This edition of this popular text continues as a comprehensive and balanced introduction to general psychiatry for students and practitioners. Updated features include the latest diagnostic algorithms, new nomenclature from DSM-IV, updated coverage of neuroscience and psychopharmacology. Includes extensive clinical vignettes and case summaries.